Descriptive account of the National Co-operative and Protective Coopers Union of America - Stewart, John M., active 1890.
Descriptive account of the National Co-operative and Protective Coopers Union of America.
Cooper.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: National Co-operative and Protective Coopers Union of America; Coopers and cooperage -- Labor unions -- United States; Coopers